1999
DOI: 10.1159/000025369
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Excitatory Amino Acid Neurotransmitters on Acid Secretion in the Rat Stomach

Abstract: Excitatory amino acids (EAAs), in particular, L-aspartate (L-Asp) neurons and their processes, were localized in the rat stomach using a immunohistochemical method with specific antibodies against either L-Asp or its synthesizing enzyme, aspartate aminotransferase (AAT). Myenteric ganglia and nerve bundles in the circular muscle and in the longitudinal muscle were found to be AAT- or L-Asp-positive. In addition, AAT- or L-Asp-positive cells were also found in the muscle layer and the deep mucosal layer. The di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2000
2000
2008
2008

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…Experimental evidence from several labs and from this laboratory ( Figure 7) have shown the GluRs to be present in the stomach, duodenum and descending colon (8,56,74,75,83). Immunohistochemical analysis showed that GluRs antibodies had poor af nity for the esophagus with the exception of anti-NMDAR 1, which preferentially stained the less mature cells within the basal layer of the strati ed squamous epithelium ( Figure 7).…”
Section: Glutamate Receptors In the Gastro-intestinal (Gi) Tractmentioning
confidence: 93%
See 1 more Smart Citation
“…Experimental evidence from several labs and from this laboratory ( Figure 7) have shown the GluRs to be present in the stomach, duodenum and descending colon (8,56,74,75,83). Immunohistochemical analysis showed that GluRs antibodies had poor af nity for the esophagus with the exception of anti-NMDAR 1, which preferentially stained the less mature cells within the basal layer of the strati ed squamous epithelium ( Figure 7).…”
Section: Glutamate Receptors In the Gastro-intestinal (Gi) Tractmentioning
confidence: 93%
“…The studies of Tsai et al (82,83) showed that Glu and Asp are both involved in regulating acid secretion in the stomach. However, their mode of action is different.…”
Section: Glutamate Receptors In the Gastro-intestinal (Gi) Tractmentioning
confidence: 99%
“…In the stomach, glutamate modulates the ability of histamine to induce acid secretion in the rat and this effect is blocked either by antagonists of AMPA or NMDA receptors [67,68]. In other studies of isolated gut segments from rats, glutamate, NMDA and KA induced concentrationdependent tonic contractions of the gastric fundus, jejunum, ileum and large intestine.…”
Section: The Gastrointestinal Tractmentioning
confidence: 94%
“…In the CNS, electrophysiological L-Glu and L-Asp are less potent than NMDA due to their avid uptake by the tissue 102 , but there appears to be an absence of the uptake processes of these compounds in the myenteric plexus 95,96 . However, Glu and Asp are both involved in regulating acid secretion in the stomach, but the mode of action of each is different 652,658 . Asp was more specific than Glu in regulating acid secretion.…”
Section: Gastrointestinal Tractmentioning
confidence: 99%